Sex differences in prevalence of metabolic syndrome components and contributing factors among psychiatric patients in Saudi Arabia - Alyousef, Ali Abdullah; Subash-Babu, Pandurangan; Alshammari, Ghedeir M.; Alabdulkareem, Kholoud B.; Yagoub, Abu ElGasim A.; Alomar, Mohammed Abdullah; Alrashed, Abdulmohsen jasem; Mohammed, Mohammed A.; Yahya, Mohammed Abdo (Frontiers in Public Health, 2025)
Background/objectivesThe purpose of this study was to detect sex differences in metabolic syndrome (MS) features and risk variables among Saudi participants.MethodsFor this study, 144 patients (52.08% males, 47.92% females) aged 19 to 59 signed a written consent form based on the Declaration of Helsinki, either as a patient or a family member. A cross-sectional survey was used to collect data on family disease history, health, and eating habits. MS components included waist circumstance (WC), high-density lipoprotein cholesterol (HDL-C), triglycerides (TGs), fasting glucose (FG), and blood pressure. A chi-square test was used to compare categorical data within and across sexes.ResultsThe associations between variables were found using Spearman correlation coefficients and simple regression analysis. Anthropometric indices were significantly (p ≤ 0.01) varied between sexes as well as family history, health behaviors, and eating behaviors. Sex variations in MS components that contributed to an MS diagnosis were discovered and were significantly varied between sexes. The most common components in males were low HDL-C (90.67%), high WC (85.33), and elevated TG levels (76.0%). In females, the most typically recognized components were high WC (86.96%), followed by high FG (69.57%) and high blood pressure and TG (63.77%). Sex differences in other risk variables for MS, such as family history, health, dietary habits, sedentary lifestyle, and smoking, were found to be associated with high anthropometric indices.ConclusionSex-specific public health policies and management techniques for preventing MS in the older adult population should be created for Saudis who are aging physiologically.